Intersectional identity, sense of LGBTQ+ community, substance use, and mental health outcomes among college students - Tuthill, Shelby Diane, author; Prince, Mark, advisor; Crain, Tori, committee member; Davalos, Deana, committee member; Faw, Meara, committee member (Colorado State University. Libraries, 2020)
Prior research has shown disparities in mental health outcomes and substance use between LGBTQ+ (lesbian, gay, bisexual, transgender, queer/questioning, and more) and non-LGBTQ+ people. Factors such as social support and LGBTQ+-specific social support have been shown to mitigate such disparities. A similar construct, sense of LGBTQ+ community has been less widely studied. In this study, LGBTQ+ (n = 154) and non-LGBTQ+ (n = 1232) undergraduate students at a large university participated in a survey. In a propensity score matched sample of LGBTQ+ students and demographically similar non-LGBTQ+ students showed no disparities in overall mood concerns, depression, anxiety, and stress; they also showed no disparities in alcohol use, cannabis use, and alcohol and cannabis co-use. Among LGBTQ+ students, sense of LGBTQ+ community was not significantly associated with mood outcomes or substance use. However, some notable disparities emerged when students were compared across racial, ethnic, gender, and sexual orientation identities simultaneously. These findings underscore the importance of an intersectional approach to research and subsequent recommendations for intervention.
Zip file contains readme document, supplementary tables via html.
Keywords: intersectionality; mental health; college; substance use; LGBTQ+